Expectation propagation based iterative group wise detection for large-scale multiuser MIMO-OFDM systems - Sheng Wu; Linling Kuang; Zuyao Ni; Jianhua Lu; Huang, Defeng David; Qinghua Guo (IEEE Wireless Communications and Networking Conference : [proceedings] : WCNC, 2014)
For the spatially correlated multiuser MIMO-OFDM channels, the conventional iterative MMSE-SIC detection suffers from a considerable performance loss. In this paper, we use the factor graph framework to design robust detection algorithms by clustering a group of symbols to combat the spatial correlation and using the principle of expectation propagation to improve message passing. Furthermore, as the complexity of detection becomes one of the issues in the design of large-scale multiuser MIMO-OFDM systems, we propose a low-complexity approximate message-passing algorithm by opening the channel transition node, which eliminates the expensive matrix inversions involved in the MMSE-SIC based algorithms. Finally, numerical results are presented to verify the proposed algorithms.